2013
DOI: 10.1073/pnas.1219922110
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Sr-substituted photosystem II at 2.1 Å resolution and its implications in the mechanism of water oxidation

Abstract: Oxygen-evolving complex of photosystem II (PSII) is a tetramanganese calcium penta-oxygenic cluster (Mn 4 CaO 5 ) catalyzing light-induced water oxidation through several intermediate states (S-states) by a mechanism that is not fully understood. To elucidate the roles of Ca 2+ in this cluster and the possible location of water substrates in this process, we crystallized Sr 2+ -substituted PSII from Thermosynechococcus vulcanus, analyzed its crystal structure at a resolution of 2.1 Å, and compared it with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
185
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 147 publications
(203 citation statements)
references
References 49 publications
(100 reference statements)
17
185
1
Order By: Relevance
“…The proton matrix ENDOR spectra of the Sr 2ϩ -substituted PSII were also very similar with those from the Ca 2ϩ -containing manganese cluster, indicating that the structure of the manganese cluster and their surrounding environment are similar in the S 2 state. The crystal structure analysis has shown that the structures of Ca 2ϩ -and Sr 2ϩ -containing manganese cluster are very similar in the S 1 state (4,21). Although the crystal structure in the S 2 state has not been reported yet, our results indicated that the structure of Ca 2ϩ -containing PSII in the S 2 state is well conserved in the Sr 2ϩ -substituted PSII.…”
Section: Methodsmentioning
confidence: 52%
See 4 more Smart Citations
“…The proton matrix ENDOR spectra of the Sr 2ϩ -substituted PSII were also very similar with those from the Ca 2ϩ -containing manganese cluster, indicating that the structure of the manganese cluster and their surrounding environment are similar in the S 2 state. The crystal structure analysis has shown that the structures of Ca 2ϩ -and Sr 2ϩ -containing manganese cluster are very similar in the S 1 state (4,21). Although the crystal structure in the S 2 state has not been reported yet, our results indicated that the structure of Ca 2ϩ -containing PSII in the S 2 state is well conserved in the Sr 2ϩ -substituted PSII.…”
Section: Methodsmentioning
confidence: 52%
“…Sr 2ϩ -substituted cyanobacterial PSII was prepared as described previously (21). The samples were suspended in a buffer containing 5% glycerol, 20 mM NaCl, 3 mM CaCl 2 (for native PSII) or 3 mM SrCl 2 (for Sr 2ϩ -substituted PSII), and 20 mM Mes/NaOH (pH 6.1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations